Vers la gestion intégrée des zones côtières en Espagne : état des lieux - José Juste Ruiz (VertigO, 2009)
The report presented by Spain to the Commission of the European Communities on March 28, 2006 shows some progress in the integrated management of coastal zones while recognizing that the achievement of an effective policy on the matter still encounters difficulties. The legal framework, centered on the Shores Law of 1988, has been exceeded by a complex reality and its implementation has been weakened by the fragmentation of the authorities acting on the littoral. The development of a national strategy on integrated management of coastal zones constitutes an important step ahead but should be followed by a more ambitious political, legislative and administrative action in order to achieve the desired results.